Nuclear terrorism: what can we learn from Los Alamos? - Volders, Brecht (Terrorism and political violence, 2019)
The international security community is increasingly concerned about the nexus between indiscriminate terrorism and the proliferation of nuclear technology and materials. Many nuclear terrorism threat assessments focus primarily on terrorist motivations to employ an atomic bomb, the availability of nuclear know-how and technology, and the opportunity for clandestine organisations to acquire fissile material. Scholars and experts, however, often neglect to elaborate on the challenges for terrorist organisations in organising and implementing the construction and detonation of a crude atomic bomb. This will most likely be a complex project. This article will therefore explore the organisation of such an endeavour. To be precise, we will highlight the impact of the organisational design of the terrorist group. The organisational design determines the division of tasks and how coordination is achieved among these tasks. It therefore has a strong impact on the functioning of any organisation, especially an innovative and complex terrorism project. Building on a case study of Los Alamos, we inductively infer that terrorist organisations face an inherent effectiveness-efficiency trade-off in designing a nuclear armament project.